De-scenting Extinction: The Promise of De-extinction May Hasten Continuing Extinctions - Campagna, Claudio (The Hastings Center report, 2017)
Among the most egregious and discouraging problems of conservation is the rapidly escalating human-caused species extinction rate. “De-extinction” refers to the application of certain cutting-edge techniques for the supposed recovery of lost species and gives the impression that scientists, enlightened and empowered by the miracles of technology, are coming to the rescue. “De-extinction” is the latest example of a long play of language that has given conservation efforts a tragically false sense of accomplishment and has worsened the conservation crisis. De-extinction is the tip of an intellectual iceberg that sits atop of a host of profoundly questionable value systems, expectations, attitudes, and priorities that elude and bewitch critical reflection. It gives the impression that extinction is reversible and, thus, diminishes the gravity of the human annihilation of species. Here, we examine how the language of de-extinction influences attitudes, shapes thoughts and imagination, and creates ethical blindness. The language developing around “de-extinction” reveals what is in fact a profound intellectual crisis at the foundation of conservation. The underlying challenge is to find the language that will articulate and inspire the radical and indispensable change needed to come to grips with the value of nature.